Plantar mechanical stimulation attenuates protein synthesis decline in disused skeletal muscle via modulation of nitric oxide level - Sergey A. Tyganov (Nature Portfolio, 2021)
Abstract Both research conducted under microgravity conditions and ground-based space analog studies have shown that air pump-based plantar mechanical stimulation (PMS) of cutaneous mechanoreceptors of the sole of the foot is able to increase neuromuscular activity in the musculature of the lower limbs. This type of stimulation is able to attenuate unloading-induced skeletal muscle atrophy and impaired muscle function. The aim of the present study was to evaluate the effects of PMS on anabolic signaling pathways in rat soleus muscle following 7-day hindlimb suspension (HS) and to elucidate if the effects of PMS on anabolic processes would be NO-dependent. The soles of the feet were stimulated with a frequency of 1-s inflation/1-s deflation with a total of 20 min followed by 10 min rest. This cycle was repeated for 4 h each day. We observed a decrease in the soleus muscle mass after 7-day HS, which was not prevented by PMS. We also observed a decrease in slow-type fiber cross-sectional area (CSA) by 56%, which significantly exceeded a decrease (–22%) in fast-type fiber CSA. PMS prevented a reduction in slow-twitch fiber CSA, but had no effect on fast-twitch fiber CSA. PMS prevented a 63% decrease in protein synthesis after 7-day HS as well as changes in several key anabolic signaling regulators, such as p70S6k, 4E-BP1, GSK3β, eEF-2, p90RSK. PMS also prevented a decrease in the markers of translational capacity (18S and 28S rRNA, c-myc, 45S pre-rRNA). Some effects of PMS on anabolic signaling were altered due to NO-synthase inhibitor (L-NAME) administration. Thus, PMS is able to partially prevent atrophic processes in rat soleus muscle during 7-day HS, affecting slow-type muscle fibers. This effect is mediated by alterations in anabolic signaling pathways and may depend on NO-synthase activity.